Judges as legislators: benevolent exercise of powers by the higher judiciary in Bangladesh with not so benevolent consequences - Islam, Md. Rizwanul (© 2016 Oxford University Commonwealth Law Journal, 2016)
This article was published in the Oxford University Commonwealth Law Journal [©2016 Published by Taylor and Francis] and the definite version is available at: http://dx.doi.org/10.1080/14729342.2016.1272943 The Article's website is at: http://www.tandfonline.com/doi/full/10.1080/14729342.2016.1272943